KAJIAN HUKUM ADMINISTRASI LINGKUNGAN TENTANG BIDANG PERIZINAN ATAS PENGELOLAAN LIMBAH PADA PABRIK KELAPA SAWIT PT. PERMATA HIJAU SAWIT - Fajar Khaifi Rizky; Suhaidi Suhaidi; Muhammad Abduh; Pendastaren Tarigan (Universitas Sumatera Utara, 2014)
Once of instrument in the effort to prevent contamination and environtment damage is an environtment approval , like in a Article 1 point 35 on the Protection and Management of the Environment which continued obeyed in Government Regulation Number 27 Year 2012 about Environtment Approval. In that provision, there are two kinds of approval environtment and protaction approval and management environmental. As a implementation from one of approval and protection and management of hazardous waste and toxic materials, in indonesia language we can called (B3) is a substance, energy, and other component which because of characteristic, consentration and it count, indirect way or indirect way, can be contaminated and destroyed the environmental, and danger of environmental, health, and also human survival and the other organism. PT. Permata Hijau Sawit as once of effort which is move in industry side of oil palm management must to complate and supply th earticle regulation which is pretend in making the document of UKL-UPL and approval to prevent contamination and environment and damage environmental. As one of the problems in a research is how to regulate about approval which have relation with the management of hazardous waste and toxic materials (B3) at oil palm factory PT. Permata Hijau Sawit. Based of that ilustration can be concluded that environment approval is one of instrument in the effort to prevent contamination and environment damage, for realize purpose of protection and management of environmental especially waste management where the substance of the licensing arrangement waste management was not complete and still need executive regulation.